New species of Pachyphloea Redtenbacher, 1906 (Phasmida: Pseudophasmatidae: Xerosomatinae) with comments on Grylloclonia Zompro, 2004 n. syn. - Murcia, Andres David; Cadena-Castañeda, Oscar J.; Noriega, Jorge Ari; García, Alexander García (Zootaxa, 2019)
We describe a new species of Pachyphloea from the Natural National Park (NNP) Chicaque, Cundinamarca in the Colombian Andes, providing data on the structure and variability of its eggs. In addition, we synonymize Grylloclonia n. syn. under Pachyphloea, and provide a key for distinguishing males and females of the known species. Finally, we discuss the taxonomical delimitation of genera within the tribe Xerosomatini, and highlight the necessity of carrying out additional studies in this particular taxon of stick insects.